2021
DOI: 10.3390/su13063552
|View full text |Cite
|
Sign up to set email alerts
|

ROS Homeostasis and Plant Salt Tolerance: Plant Nanobiotechnology Updates

Abstract: Salinity is an issue impairing crop production across the globe. Under salinity stress, besides the osmotic stress and Na+ toxicity, ROS (reactive oxygen species) overaccumulation is a secondary stress which further impairs plant performance. Chloroplasts, mitochondria, the apoplast, and peroxisomes are the main ROS generation sites in salt-stressed plants. In this review, we summarize ROS generation, enzymatic and non-enzymatic antioxidant systems in salt-stressed plants, and the potential for plant biotechno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 116 publications
2
57
0
Order By: Relevance
“…However, the disturbance of cell homeostasis due to ion imbalance generates ROS [81,82]. Excessive ROS accumulation in plant cells leads to numerous changes and damages, which in turn affect the condition of the plant, its yield and survival [83]. This could affect DNA, chlorophyll, enzymes and other proteins, which may lead to detrimental effects, and finally even cell death [20,[84][85][86].…”
Section: Salinizationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the disturbance of cell homeostasis due to ion imbalance generates ROS [81,82]. Excessive ROS accumulation in plant cells leads to numerous changes and damages, which in turn affect the condition of the plant, its yield and survival [83]. This could affect DNA, chlorophyll, enzymes and other proteins, which may lead to detrimental effects, and finally even cell death [20,[84][85][86].…”
Section: Salinizationmentioning
confidence: 99%
“…These processes have a decisive influence on the condition of the plant and their development [6,9,[80][81][82]. Reducing the impact of plant diseases caused by pathogens, mitigating abiotic stress or inducing systemic resistance in competition for nutrients and niches are categorised as indirect mechanisms [6,83]. The most common and successful PGPB belong mainly to the genera Agrobacterium, Azospirillum, Azotobacter, Bacillus, Burkholderia, Pseudomonas, Streptomyces and Serratia [52,84].…”
Section: About Pgpbmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a Food and Agriculture Organisation (FAO) report, many people still experience food shortages. Moreover, the requirements for food will gradually increase in the world, at least until 2030 [1]. Permanent pesticide, herbicide, and fungicide use, and climate change induce soil degradation and crop losses [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relationship between plants and nanoparticles (NPs) has attracted scientists' attention, especially to its application in agricultural production as nanonutrition. It has been shown that a small number of different NPs are present in agricultural soil which have been shown to accumulate in plants [1].…”
Section: Introductionmentioning
confidence: 99%